Mother earth, father sky Sue Harrison - Harrison, Sue (New York Doubleday, 1990)
Chagak, a young Native American woman living during the Ice Age, sees an enemy tribe massacre her family, is forced to bear the child of her enemy, and embarks on a personal quest for survival and revenge
61676
Keywords: Indians of North America; Prehistoric peoples